Antibacterial Activity of Carotenoid Pigments Produced by Heterotrophic Bacteria from Seawater in Krakal Coastal Area, Yogyakarta, Indonesia - Rina Septriani Sidin; Endah Retnaningrum (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2022)
Investigating natural pigments resulting from marine bacterial secondary metabolites is important because of their broad benefits in the food, pharmaceutical, cosmetic, and textile industries. In this study, 52 isolates of pigmented bacteria were isolated from seawater in the Krakal coastal area, Yogyakarta, Indonesia. Seven bacterial isolates showed high pigment stability. Profiling of pigment extracts using a mixture of acetone and methanol with UV–Vis spectrophotometric reading showed that the compounds produced were carotenoids. The highest total carotenoid content with UV–Vis spectrophotometric reading at 480 nm was produced by the Kral-3 isolate (1800 mg/g), followed by Kral-15 (1698.9 mg/g) and Kral-25 (797.2 mg/g) isolates. Analysis of the antibacterial activity of the carotenoid extracts of Kral-3, Kral-15, and Kral-25 isolates using the agar well diffusion method revealed a very strong inhibition score against Escherichia coli. In addition, the carotenoid extract of the Kral-3 isolate showed a strong inhibition score against Staphylococcus aureus, whereas the Kral-15 and Kral-25 isolates showed moderate inhibition scores. Based on the 16S rRNA gene analysis, the Kral-3, Kral-15, and Kral-25 isolates were identified as Kocuria rhizophilla, Calidifontibacter sp., and Rhodococcus ruber, respectively. Based on the findings, the novel bacterial strains are a potential bioresource for the commercial production of natural carotenoids.